2004
DOI: 10.1007/s10024-003-1006-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytokeratins 7 and 20 in Helicobacter pylori-associated Chronic Gastritis in Children

Abstract: Helicobacter pylori gastric infection induces structural changes in the gastric epithelium. Among them, variations in the expression of cytokeratins have been reported in adult patients. In the present study, we describe the expression of CK7 and CK20 in gastric samples taken from the antrum in three groups of pediatric patients: (A) Helicobacter pylori-associated chronic gastritis (mean age: 11.4 years); (B) previous H. pylori chronic gastritis patients (mean age: 9.4 years); and (C) controls (mean age: 8.8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The frequent association of CK7 expression with epithelial areas connected with active inflammation is noteworthy. Similar results have been observed in biopsies from the gastric mucosa in a study of patients with gastritis (28).…”
Section: Discussionsupporting
confidence: 87%
“…The frequent association of CK7 expression with epithelial areas connected with active inflammation is noteworthy. Similar results have been observed in biopsies from the gastric mucosa in a study of patients with gastritis (28).…”
Section: Discussionsupporting
confidence: 87%
“…Only 17 studies included in our review reported the presence of LF with a mean of 46.4% in H pylori-positive versus 17.8% in H pylori-negative children. Moreover, H pylori-positive children showed significantly higher 3.83 RR for LF (Table 2) (8,12,14,17,18,27,34,35). According to the literature, the presence of LF is highly specific of H pylori infection but not particularly in children (12,17,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there were no significant differences in overall survival (OS), local control, and freedom from distant metastases over 2 years between the 2 groups. 54,55 In a more recent trial, the prospectively randomized NCT 00003052 phase III multicenter trial, 341 patients with untreated localized high-risk STS were enrolled, of whom 169 received neoadjuvant chemotherapy consisting of etoposide, ifosfamide, and adriamycin (EIA) plus regional hyperthermia, and the remainder received EIA alone. After induction therapy, the tumor response was evaluated by imaging, and the best local treatment (surgery and/or RT) was selected, followed by another 4 cycles of induction therapy.…”
Section: Hyperthermia Combined With Chemotherapymentioning
confidence: 99%
“…Furthermore, there were no significant differences in overall survival (OS), local control, and freedom from distant metastases over 2 years between the 2 groups. 54,55…”
Section: Clinical Use Of Hyperthermiamentioning
confidence: 99%